STRUKTUR SIMBOLIK TARI TOPENG PATIH PADA DRAMATARI WAYANG TOPENG MALANG DI DUSUN KEDUNGMONGGO - Soerjo Wido Mintarto (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
Dramatari   Wayang  Topeng  Malang  reflects  the  life  style  of  the Malangese. They are believed to have historical relevance with the development Malang s oldest culture which was under the reign of Kanjuruhan Kingdom around 7th   century.  Topeng  Patih  dance,  the  opening  dance  of  the  traditional  theatre performance are closely related to the pattern of the show related to the space, time, and content. So the symbolic structuralist theoretical approach would be the chosen strategy to understand the symbolic internal meanings. The analysis indicates that the choreographic structure of Tari Topeng Patih consists of 7 elements: character, ritual, communication, body movement, make up and wardrobe art, instrument, and stage for the performance. All of them are oriented towards the grandeur of refined character or attitude